Analysis of the Impact of Sustainable Marketing Strategic on Consumer Preferences - Hamisi, Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2024)
Sustainable marketing strategies have become an increasingly important topic in the business world. Based on Nielsen Indonesia data in 2021, around 83% of Indonesian consumers stated that they prefer products from brands that are committed to environmentally friendly business practices, but even though consumers express support for sustainable products, their purchasing behavior is not always consistent with this statement. This study aims to analyze the impact of sustainable marketing strategies in influencing consumer preferences and purchasing decisions. The research method uses a quantitative survey. The sample consisted of 400 randomly selected respondents. Data collection was carried out through a structured questionnaire, and data analysis used confirmatory factor analysis (CFA) and moderation regression. The results of the study show that sustainable marketing strategies have a significant influence on consumer preferences. Environmental awareness and social norms strengthen this relationship as significant moderating factors. Integration of sustainable strategies can increase product appeal and strengthen brand image in a competitive market, with a focus on strengthening sustainability communication to maximize the positive impact of sustainable marketing strategies.